2004
DOI: 10.1111/j.1067-1927.2004.012205.x
|View full text |Cite
|
Sign up to set email alerts
|

Autologous cultured keratinocytes on porcine gelatin microbeads effectively heal chronic venous leg ulcers

Abstract: We have established a specific bioreactor microcarrier cell culture system using porcine gelatin microbeads as carriers to produce autologous keratinocytes on a large scale. Moreover, we have shown that autologous keratinocytes can be cultured on porcine collagen pads, thereby forming a single cell layer. The objective of this study was to compare efficacy and safety of autologous cultured keratinocytes on microbeads and collagen pads in the treatment of chronic wounds. Fifteen patients with recalcitrant venou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 42 publications
1
37
0
Order By: Relevance
“…In a recent study, diabetic mice transplanted with islets, seeded into collagen IV-coated macroporous gelatin scaffolds into the epididymal fat pad achieved euglycaemia that was maintained for up to 297 days, and showed a normal glucose response when challenged with an IPGTT [Salvay et al, 2008]. Encouraging results have also been shown in clinical trials with the transplantation of autologous keratinocytes seeded into gelatin microbeads in the healing of chronic leg ulcers [Liu et al, 2004]. Our study using Gelitaspon as the scaffold demonstrated islet survival and function in the short term.…”
Section: Discussionmentioning
confidence: 94%
“…In a recent study, diabetic mice transplanted with islets, seeded into collagen IV-coated macroporous gelatin scaffolds into the epididymal fat pad achieved euglycaemia that was maintained for up to 297 days, and showed a normal glucose response when challenged with an IPGTT [Salvay et al, 2008]. Encouraging results have also been shown in clinical trials with the transplantation of autologous keratinocytes seeded into gelatin microbeads in the healing of chronic leg ulcers [Liu et al, 2004]. Our study using Gelitaspon as the scaffold demonstrated islet survival and function in the short term.…”
Section: Discussionmentioning
confidence: 94%
“…For example, epidermal and dermal cell-seeded microcarriers enhanced skin healing 14,15 and hepatocyte-seeded microcarriers have been shown to restore liver function in rats. 16 Microcarrier-cultivated porcine chondrocytes implanted into full-thickness porcine cartilage defects outperformed chondrocytes propagated in monolayers.…”
mentioning
confidence: 99%
“…To realize the lTPs, a dynamic cell seeding on gelatine porous microcarriers was used. It has been suggested that the macroporous structure of CultiSpher microcarriers creates a suitable environment for the development of fibroblasts, as the cells within the interior will experience lower shear forces than those encountered with nonporous carriers [19][20][21]. Moreover, fibroblasts proliferating on macroporous gelatine based-microcarriers are able to synthesize a tissue with a dermal-like appearance [15].…”
Section: Resultsmentioning
confidence: 99%